Ethylbenzene oxidation over KIT-6 mesoporous silica-based hybrid supported catalysts - Chaudhary V.; Sharma S. (My University, 2025)
Mesoporous silica-based hybrid supported catalysts were demonstrated for ethylbenzene oxidation to acetophenone. Mesoporous silica support was synthesized by the sol–gel technique. In-house synthesized silica particles were impregnated over commercially available polystyrene polymer support for the synthesis of hybrid supports. The incipient impregnation method was employed to synthesize hybrid supported Co (II) and Cu (II) catalysts. A catalytic activity test was demonstrated for ethylbenzene oxidation at different reaction conditions. Acetophenone with 99.79% selectivity was obtained as a primary reaction product. Synthesized catalysts were compared with the catalysts reported earlier in the literature. © 2021, The Polymer Society, Taipei.